1992
DOI: 10.1002/eji.1830220402
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific migration pathways by phenotypically distinct subpopulations of memory T cells

Abstract: A proportion of T cells recirculate in a tissue-selective manner. Recent studies which showed that the skin-tropic subset of T cells was of memory/activated type, led us to examine whether the preferential homing of T cells to the gut also involved memory T cells, and if so whether these memory T cells were phenotypically distinct from other memory T cells. Lymphocytes migrating through the gut and the skin of sheep was collected by cannulating the lymphatic ducts draining these tissues. Both naive and memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(137 citation statements)
references
References 48 publications
9
128
0
Order By: Relevance
“…retransfusion [74]. Naïve and memory lymphocytes were analysed in sheep and their tissue specific immigration was obvious [41][42][43]. Based on these experiments, the concept about naïve and memory T cells was clarified.…”
Section: Important Intestine-related Lymphocyte Migration Studies In mentioning
confidence: 99%
See 2 more Smart Citations
“…retransfusion [74]. Naïve and memory lymphocytes were analysed in sheep and their tissue specific immigration was obvious [41][42][43]. Based on these experiments, the concept about naïve and memory T cells was clarified.…”
Section: Important Intestine-related Lymphocyte Migration Studies In mentioning
confidence: 99%
“…Expression of α4β7-integrin has been demonstrated on memory T cells of sheep which migrate through intestinal lymph nodes and PP [41]. Likewise, high levels of α4β7-integrin were detected on lymphocytes in ovine intestinal lymph, whereas expression in peripheral or pulmonary lymph was low [1,42]. MAdCAM-1 was detected at high levels on HEV of mesenteric lymph nodes and PP as well as on postcapillary venules of the intestinal lamina propria, whilst tonsils and peripheral lymph nodes were only weakly positive [41,66].…”
Section: Regulation Of Lymphocyte Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…All mAbs used in this study have been described previously: IL-A42, anti-bovine CD2 [15]; IL-A11, anti-bovine CD4 [4]; IL-A51, anti-bovine CD8 [17]; R15.7, anti-canine CD18 cross reactive with bovine CD18 [6,18]; BII 218.1, antisheep CD49d crossreactive with bovine cells [25]. UD15 directed against chloramphenicol [39] served as negative control.…”
Section: Cell Surface Phenotyping By Flow Cytometrymentioning
confidence: 99%
“…Previous experiments have indicated that memory CD4 ϩ T cells are largely responsible for tissue-specific recirculation patterns observed using recirculating ELLs in vivo (23,26,27). To test for the possibility that a single lymphocyte subset was responsible for the observed tissue-specific homing patterns of PBLs, labeled lymphocytes were collected from efferent intestinal or s.c. lymph at 12, 24, and 36 h after i.v.…”
Section: ␥␦-T Cells Are the Major Recirculating Populationmentioning
confidence: 99%